Offending users: designing-in deterrence with mobile telephones - John McCardle; Ian Storer; George Torrens; Shaun Whitehead; Jen Mailley; Graham Farrell (2011)
This paper describes research relating to the design semantics of desirable products and the crime of theft. The methods employed range from the review of existing designs of mobile phones and associated systems and technologies, the perception of crime from a student designer's viewpoint and, importantly, the opinions of young offenders about proposed design solutions. We developed conceptual designs in consultation with the Mobile Data Association and these were reviewed by a sample of groups of young offenders and 'non-offender' consumers of similar age, to reflect the different user perspectives. The conclusions reveal differences between offenders and non-offenders in their perceptions of the deterrent effect of different design solutions. It is suggested that the research offers insight into the use of empathic strategies in the design of frequently stolen 'hot products'.